2005
DOI: 10.2106/jbjs.e.00535
|View full text |Cite
|
Sign up to set email alerts
|

Operative Management of Displaced Femoral Neck Fractures in Elderly Patients

Abstract: While surgeons prefer internal fixation for younger patients and arthroplasty for older patients, they disagree about the optimal approach to the management of patients between sixty and eighty years old with a displaced fracture and active patients with a Garden type-III fracture. Surgeons also disagree on the optimal implants for internal fixation or arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
336
1
15

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 419 publications
(356 citation statements)
references
References 7 publications
4
336
1
15
Order By: Relevance
“…uncemented hemiarthroplasties using a proximal press-fit design showed excellent results [2], but other results of uncemented hemiarthroplasties, often using stems different from those in THA, are more uncertain. The uncemented Austin Moore prosthesis (Howmedica, Rutherford, NJ) is commonly used [3], and several randomized trials included in review articles include the results of this specific implant. One randomized trial reported better results regarding pain when using an uncemented HA-coated implant in comparison to results with the Austin Moore prosthesis [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…uncemented hemiarthroplasties using a proximal press-fit design showed excellent results [2], but other results of uncemented hemiarthroplasties, often using stems different from those in THA, are more uncertain. The uncemented Austin Moore prosthesis (Howmedica, Rutherford, NJ) is commonly used [3], and several randomized trials included in review articles include the results of this specific implant. One randomized trial reported better results regarding pain when using an uncemented HA-coated implant in comparison to results with the Austin Moore prosthesis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-six surgeons performed a median of five operations each (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Patients underwent a bipolar The cemented stem is a straight, collared stem made of a cobalt-chromium alloy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-six surgeons performed a median of five operations each (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Patients underwent a bipolar hemiarthroplasty with either a cemented femoral stem (Spectron; Smith & Nephew, Memphis, TN, USA) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Many types of arthroplasties are used to treat displaced fractures of the femoral neck in the elderly [1]. There is some evidence of inferior short-term results with decreased mobility and pain when using an uncemented implant, but the diversity of implants used in clinical trials represents a problem [19].…”
Section: Introductionmentioning
confidence: 99%